Wearing Your Heart on Your Sleeve:K-pop Merchandise in Validating Identity - Mohammed, Sharifah Faizah Syed; Balqis, Nur Maizatul (Universitas Negeri Semarang, 2025)
K-pop merchandise plays a vital role in shaping fan identity, functioning beyond its commercial value. This study explores how merchandise enables identity construction and social belonging within the global K-pop fandom. This research employs qualitative discourse analysis of X (formerly Twitter) tweets and a survey of pertinent literature on fandom and material culture to delineate four principal functions of merchandise: as emblems of loyalty, instruments for active participation, rites of passage, and enablers of community connectedness. The results indicate that items like lightsticks and photocards serve as emotional and symbolic anchors, signifying personal achievements and facilitating social relationships. These objects enable fans to transition from passive consumers to active cultural participants, thereby strengthening identification through ritualized actions and shared beliefs. This study suggests that K-pop items function as hybrid objects—economically valued, emotionally significant, and culturally relevant. It provides insights into the intersection of material culture and identity formation in modern fandoms, especially within the performing arts sectors that generate and uphold idol culture.